Penerapan Relaksasi Benson terhadap Tingkat Dismenorea Pada Remaja di Desa Glodogan, Klaten - Alda Vanty Octavia; Dewi Kartika Sari (Jurnal Anestesi, 2023)
Background: Dysmenorrhea is discomfort in the lower abdomen spreading to the waist which is often experienced by young women aged 12-18 years or even almost all women during menstruation, usually often felt before menstruation or during menstruation. Benson relaxation technique is one of the complementary therapies developed as a relaxation technique that is simple and easy to implement and is a combination of relaxation response techniques with individual belief systems or faith factors. Purpose : Knowing changes in the level of dysmenorrhea in adolescents before and after doing benson relaxation therapy. Method: this application with descriptive research methods and observing events or events that have occurred. Descriptive research is research conducted to describe or describe an event that occurs. Results: handling dysmenorrhea with benson relaxation therapy given for 2 days with 1 time a day for 15 minutes can affect the patient's level of dysmenorrhea so that there are changes in the patient's pain scale. Conclusion: Benson relaxation therapy can reduce the level of dysmenorrhea in adolescents who are experiencing menstrual pain.